Study of the rs1800795 polymorphism of the IL6 gene to verify the clinical portrait of a patient with chronic heart failure: gender aspects - Elena V. Khazovа; Olga V. Boulashova; Elena V. Valeeva (ZAO "Consilium Medicum", 2022)
Background. Genetic studies in cardiology allow to identify predisposition and predict the course of multifactorial cardiovascular diseases by identifying the association of polymorphic loci of candidate genes with the clinical phenotype. One of these diseases associated with poor prognosis is chronic heart failure (CHF). Activation of pro-inflammatory cytokines is one of the key aspects of the development and progression of CHF. Aim. To identify the features of the clinical course of CHF of ischemic etiology in patients, taking into account the gender and genotype of the rs1800795 polymorphism of the IL6 gene. Materials and methods. Four hundred fourteen patients of both sexes with stable CHF of ischemic origin, aged 66.410.4 years, were included. Clinical characteristics of men and women of each genotype of the rs1800795 polymorphism of the IL6 gene were compared. Genotyping of the rs1800795 polymorphism of the IL6 gene was performed by real-time polymerase chain reaction. Results. In male patients with CHF, the frequency of allele C was higher than in the control group (p=0.04). Homozygous carriers of the C allele showed a greater risk of developing atrial fibrillation (p=0.021). In terms of biochemical parameters, in patients with a heterozygous genotype, compared with homozygotes for the G allele of the rs1800795 polymorphism of the IL6 gene, the levels of cholesterol, triglycerides (TG), cholesterol not associated with high-density lipoproteins (non-HDL-cholesterol) were higher (p=0.044, p=0.019, p=0.016). Patients with the CC genotype of the rs1800795 polymorphism of the IL6 gene females compared with men were more likely to have IIIIV functional class of CHF (p=0.001) and had a high heart rate (p=0.021). Male patients of the CG genotype were more likely to undergo coronary interventions (p=0.001). In women of the CG genotype, CHF was more often combined with DM (p=0.015), the level of non-HDL-cholesterol (p=0.04) was higher, and glomerular filtration rate was lower than in men (p=0.001). Comparison of the GG genotype revealed a higher incidence of chronic kidney disease in women (p=0.022). Women had significantly lower glomerular filtration rate (p=0.001), systolic blood pressure (p=0.004). The level of such biochemical parameters as cholesterol (p=0.001), TG (p=0.019), low-density lipoprotein cholesterol (p=0.002) was reduced, except for high non-HDL-cholesterol (p=0.001). There were more men with left ventricular ejection fraction 40% (p=0.009), women with left ventricular ejection fraction 50% (p=0.002). Conclusion. The identified phenotypic and gender differences create prerequisites for determining patient-oriented genetic risk, opening up new opportunities for preventing the progression and complications of CHF.